Development of an Oxygen Mass Transport Coefficient Measurement and Separation Method for Proton Exchange Membrane Fuel Cells. (8th September 2020) - Buehre, Lena Viviane; Suermann, Michel; Hanke-Rauschenbach, Richard; Bensmann, Boris; Bethune, Keith; St-Pierre, Jean
Abstract : In this work, we use a method to separate the total oxygen mass transport coefficient into molecular, Knudsen, and ionomer contributions. Therefore, limiting current density measurements are carried out as a function of the diluent gas (He, N2, CO2 ), temperature (30, 50, 80°C), relative humidity (50, 75, 100%), and oxygen concentration (1, 3, 5, 7%) using state of the art membrane electrode assemblies with three platinum loadings (0.05, 0.1, 0.15 mg/cm 2 ). As expected, the molecular diffusion coefficient is independent of the platinum loading, but increases with temperature to a varying degree depending on the humidity level. On the other hand, the Knudsen diffusion coefficient increases with increasing electrochemical active surface area and temperature, and with decreasing relative humidity. The separation procedure includes a novel feature to isolate the ionomer mass transport resistance. Its interpretation as well as the method's reliability are critically questioned using operating condition dependencies.